To speak or not to speak: How public relations can influence authentic corporate social advocacy and support organizational reputation - Wilkinson, Julia (My University, 2024)
Over the past decade, organizations have faced pressure to speak out on divisive social and political issues, a practice scholars define as corporate social advocacy (CSA). Although there are benefits to engaging in CSA, CSA also carries inherent risks, including to organizational reputation. As such, several scholars posit that CSA has emerged as an important function of the public relations practice. This capstone furthers the research on this theory through the following thesis: when public relations professionals are given the autonomy and have the influence to use ethical decision-making frameworks in guiding their organization’s CSA efforts, the CSA is more likely to be authentic and positively impact the organization’s reputation. Academic literature on CSA, public relations excellence, ethics, and reputation formed the foundation of a normative theory, which the researcher tested through a survey and in-depth interviews with public relations professionals at Canadian and American corporations. Results demonstrate that most public relations professionals are empowered to participate in their organization’s CSA decision-making and strategy development, which drives authentic CSA and may contribute to a positive organizational reputation. Moreover, public relations professionals who consider ethics in their CSA decision-making are more likely to achieve authentic CSA. This research surfaced practical recommendations for promoting authentic CSA that may contribute to organizational reputation.
Keywords: corporate social advocacy; public relations; communication; ethics; reputation; issues management